Overexpression of Cancer-Associated Genes via Epigenetic Derepression Mechanisms in Gynecologic Cancer - Jeong, Hae Min; Kwon, Mi Jeong; Shin, Young Kee (Frontiers in Oncology, 2014)
Like other cancers, most gynecologic cancers caused by aberrant expression of cancer-related genes. Epigenetics is one of important gene expression mechanisms which contribute to cancer development and progression by regulating cancer-related genes. Since the discovery of differential gene expression patterns in cancer cells compared with normal cells, extensive efforts have been made to explore the origins of abnormal gene expression in cancer. Epigenetics, the study inheritable changes in gene expression that do not alter DNA sequence, is a key area of this research. DNA methylation and histone modification are well-known epigenetic mechanisms, microRNAs and alternative splicing have recently been identified as important regulators of epigenetic changes. These epigenetic mechanisms not only affect specific target gene expression but also regulate the functioning of other epigenetic mechanisms. Moreover, these diverse epigenetic regulations occur simultaneously. Epigenetic regulation of gene expression is extraordinarily complicated and requires that all epigenetic mechanisms be studied at once to determine the exact gene regulation mechanisms. Traditionally, the contribution of epigenetics to cancer is thought to be mediated through the inactivation of tumor suppressor genes (TSGs) expression. But recently it is arising that some oncogenes or cancer-promoting genes (CPGs) are overexpressed in diverse type of cancers through epigenetic derepression mechanism, such as DNA demethylation, histone demethylation. Epigenetic derepression arises from diverse epigenetic changes, and all of these mechanisms are actively interact each other to increase oncogenes or CPGs expression in cancer cell. Oncogenes or CPGs overexpressed through epigenetic derepression can initiate cancer development, and the accumulation of these abnormal epigenetic changes makes cancer more aggressive and resistant to treatment. This review discusses epigenetic mechanisms involved in the overexpress